Pengaruh Pelaksanaan Konseling dan Pendampingan Suami terhadap Keberhasilan Ibu Menyusui dalam Pemberian Kolostrum - Nuraeni Nuraeni; Suryani Soepardan; Bahiyatun Bahiyatun; Ari Soewondo (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2014)
The provision of colostrum to newborns needs to be improved and promoted with the campaign targets not only pregnant women and nursing mothers but also the husbands. Husbands’ support in the form of continuous assistance is indispensable for the successful provision of colostrum and it is expected that husbands are able to guide, support and direct their wife to give colostrum to their infants. This study aimed to determine the effect of counseling on husbands and the husbands’ assistance in the successful provision of colostrum. This was a quasi experimental study using a post -test only with control group design. The samples were 30 consisting of 15 in the study group and 15 in the control group. The analysis on the effect of counseling in this study used chi square test. The results showed that the respondents given counseling and with husbands’ assistance had a 2.333 times greater chance to give colostrum to their infants compared with those without counseling and husbands’ assistance (p = 0.007, RR = 2.333). A given counseling and with husbands’ assistance had effect greater on the success of lactating mothers in the provision of colostrums. Midwives apply counseling and husbands’ assistance in pregnant women and lactating mothers in order to give colostrum to their infants.